Optimization Strategy for Formaldehyde Removal by Carbon Cathode Electro-Fenton Enhancement of Formaldehyde and Oxygen Co-adsorption by Rational Nitrogen Doping Types - Yang, Lei (Langmuir : the ACS journal of surfaces and colloids, 2024)
This study investigates the effect of N-doped coal-based activated carbon cathode on formaldehyde-oxygen coadsorption. Further investigation investigates the effect of formaldehyde-oxygen coadsorption on H2O2 generation and formaldehyde removal in an electro-Fenton system. Nitrogen doping enhances formaldehyde and oxygen coadsorption by modulating competitive adsorption. Density Functional Theory (DFT) calculations confirm pyrrole nitrogen favors formaldehyde, and graphite nitrogen favors oxygen adsorption. N-doped activated carbon adsorbs 0.36 mg of formaldehyde and 0.1 mg of oxygen in 120 min and removes 82.43% of formaldehyde after electro-Fenton treatment. N-doped activated carbon enhances the synergistic adsorption of formaldehyde and oxygen. In the synergistic adsorption process, the amount of formaldehyde adsorbed is greater than the amount of oxygen adsorbed. This improves the removal efficiency of formaldehyde by electro-Fenton technology. It provides a new method for electro-Fenton removal of organic pollutants